The association between sport specialisation and movement competency in youth: a systematic review - Zoellner, A.; Whatman, C.; Read, P.; Sheerin, K. (International Journal of Sports Science & Coaching, 2021)
Negative long-term outcomes have been reported following sport specialisation including increased injury risk. The underlying mechanisms remain unclear; however, fewer exposures to broad ranging movement patterns and reductions in movement competency have been suggested. This review synthesised the evidence to examine if an association is present between sport specialisation and movement competency.